Analysis of soil seed bank in the seasonal deciduous forest Alto Uruguay -RS - Lazzari, Laudison; Georgin, Jordana; Borba, Willian Fernando de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Temporal changes in floristic composition of a community, as well as seasonal variations in fruiting and dispersal influence the abundance of seeds, the number of species and forms of life available in the soil of a forest. This study aimed to analyze the composition and density of tree species present in the soil seed bank, compared with border and interior, comparing the different seasons of the year, present in each sample unit that occurred in three fragments of a Deciduous Forest located at 27 ° 23 '45 "SE 53 ° 25' 53" W in the municipality of FredericoWestphalen, RS, Brazil. For the assessment will be collected 48 samples in each of these fragments, 24 samples at the edge, 12 points and 24 equally spaced samples in the forest, 12 random points, totaling 144 samples per seasonal period, made in three months in each of the different fragments. The first sampling was performed in August 2010. There was no significant difference in the density of the soil seed bank in relation to distances, and no influence of edge effect.